Assessing the Antimicrobial and Neonatal Diabetes Potential of Phytol from Scoparia dulcis: A Combined Computational and Experimental Approach - Mary, Arulandhu Clara; Aishwariya, Sowntharrajan; Viji, Murugesan; Vijayalakshmi, Periyasamy; Rajalakshmi, Manikkam (Journal of Neonatal Surgery, 2025)
Natural products from medicinal plants offer a safe alternative to conventional medicine for the treatment of various diseases, especially microbial infections burdened by microbial resistance, as well as metabolic disorders such as neonatal diabetes. In this study, we performed a screening study of the plant Scoparia dulcis for phytol for both anti-microbial activity and potential modulatory activity on neonatal diabetes-associated targets using in silico method. Phytol was docked in key microbial enzymes as well as neonatal diabetes targets. Phytol had the highest docking affinities with dihydrofolate reductase and lanosterol 14α-demethylase with the use of molecular docking. Additionally, phytol also had a good docking score towards KCNJ11 and ABCC8 implying it may modulate insulin secretory pathway. In vitro, Scoparia dulcis leaf water extract has also shown a inhibition of Escherichia coli in disc diffusion assay. Therefore, together these results suggest that phytol's molecular activities may be beneficial, acting as an antimicrobial agent but also potentially suggesting a therapy for neonatal diabetes.